CESifo World Economic Survey February 2012 - Johanna Plenk; Gernot Nerb; Klaus Abberger; Steffen Elstner (CESifo World Economic Survey, 2012)
World Economy: Positive outlook almost across the board - Western Europe: Economic expectations brighten - North America: Economic climate indicator continues to rise - Eastern Europe: More positive expectations - CIS: Solid performance - Asia: Economic climate indicator starts to rise again - Oceania: Economic climate indicator drops - Latin America: Economic climate friendlier - Near East: Buoyant economic climate - Africa: No unified economic trend
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies